Pernikahan Beda Agama: Tafsir Ideologis Ezra 10: 1-44 dengan Lensa Pluralisme Agama - Daniel Luther Shindang (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2021)
In today's context, the level of religious intermarriage is increasingly questionable and negative. Even such negative imagery is legitimized by bible texts, for one thing: Ezra 10: 1-44. The text of Ezra 10: 1-44 explicitly shows Ezra's action against intermarriage between the Israelites and foreign nations. Such resistance is based on understanding that when the Israelites mix with foreigners their allegiance to YHWH is eroded. This post is the result of ideological criticism with a pluralism perspective on Ezra 10: 1-44. Interpretations reveal that the prevailing ideology that represented Ezra 10: 1-44 was the attempt to maintain the purity of the cult YHWH. Thus, the writer finds it necessary to do a dialectic with the problem of religious interfaith that takes place in today's context. The dialectic done was to find a correlation between the context of Ezra and current readers. On the other hand, based on the ideological theories of sheila brigs and Robert Setio, the writer offers a counter-ideology, producing a theological offer in the plural context of Indonesia.